DEVELOPMENT OF AUDIOVISUAL MEDIA "DIGESTOPIA" BOARD GAME TO ENHANCE PROBLEM-SOLVING SKILLS AND COGNITIVE LEARNING OUTCOMES OF HIGH SCHOOL STUDENTS - Febriyanti, Riska Dwi; Al-Muhdhar, Mimien Henie Irawati; Hassan, Zainudin; Setiawan, Deny; Sumberartha, I Wayan; Wulandari, Nuning; Yuhanna, Wachidatul Linda; Fanani, Zainal (Jurnal Pendidikan Matematika dan IPA, 2025)
Students at SMAN 1 Singosari continue to demonstrate limited problem-solving skills and cognitive learning outcomes, partly due to contextually irrelevant media and reliance on LCD projectors. This study aimed to evaluate the validity and practicality of "Digestopia", an audiovisual, website-assisted electronic board game developed using the RICOSRE model (Reading, Identifying problem, Constructing solution, Solving the problem, Reviewing the problem solving, and Extending problem solution) and integrated with the SDGs' Zero Hunger initiative (Sustainable Development Goal 2: Zero Hunger). The development process adopted the Lee and Owens instructional design model, which consists of four stages: analysis, design, development, and evaluation. Data were collected using expert validation sheets and student response questionnaires and analyzed using descriptive quantitative techniques to determine the average scores. The results showed that "Digestopia" was valid (90.6%) and practical (86.7%) for classroom use, indicating its potential as an interactive learning tool.